Cartório na maternidade reduz o sub registro? Análise para o programa minha certidão em Pernambuco e o projeto de erradicação do sub registro do Ceará - Vasconcelos, Ramon Lucas Almeida (2022)
With sub levels record more than 30%, the Brazilian government in 1997 enacted the Law No. 9534, which guaranteed nationwide gratuitousness of the first civil registration and birth certificate for all citizens, believing that one of the major factors contributing to the high level of under Brazilian register were the costs that the citizen had to pay to do so. In 2009, by Act No. 15213 was launched the pilot project Minha Certidão Program, that has the main objective of universal access to birth records in the state of Pernambuco. A similar project with the same objective was also set up in the State of Ceará implemented through a provision of the National Justice Council (CNJ). The decision to invest in such programs, based on the assumption that there will be a positive impact on the result set of collective interest or individual, which subsequently should bring benefits to society. Thus, for the Program Impact Assessment it was used the Differences in Differences method in conjunction with the logit model, given the nature of the used impact index. According to the results, the groups that participated in the program showed reductions in their sub record levels well above to non-participating groups. Moreover, it was also made a study that showed various forms of monetization of benefits of the program, both for states and cities, in the form of getting revenue from the Union, as to the citizen which through the Civil Registry, can participate on various social assistance programs.